Outcomes of Refractive Surgery Consultations at an Academic Center: Characteristics Associated with Proceeding (or Not Proceeding) with Surgery - Irene C. Kuo; Benjamin Lee; Jiangxia Wang (Journal of Ophthalmology)
Objective. Refractive surgery volume has not rebounded despite economic recovery and literature describing safety, efficacy, and high patient satisfaction. We sought to examine characteristics of consultation seekers and status after consultation. Methods. Charts of patients seeking refractive surgery at Johns Hopkins University from 2013 through 2016 were retrospectively reviewed for age, gender, refractive characteristics, and outcome: surgery (photorefractive keratectomy, laser in-situ keratomileusis, implantable collamer lens, or refractive lens exchange); no surgery—“lost candidate” (good candidates who were lost after consultation); noncandidates based on technological limitations or contraindications; or no surgery—possessing expectations that surgery would not meet. Associations between characteristics and status after consultation were examined. Results. Twenty percent (142/712) of all patients were “lost candidates”; 57% (408/712) completed surgery. More women (56% or 401/712) sought consultation, but a greater percentage (63% or 195/311) of men completed surgery than women did (53% or 213/401) p=0.02. Of consultation seekers, 60% were low myopes, 29% were high myopes (>6 diopters of myopic spherical equivalent), and 11% were hyperopes. Surgical patients’ mean age was 34.2 ± 10.2 (standard deviation) years; for each additional year of age, patients were less likely to have surgery p<0.001. Hyperopes were ≥3 times more likely than myopes to have expectations not met by surgery or to be noncandidates than to have surgery p<0.005. Conclusions. Most patients seeking refractive surgery had 6 diopters or less of myopia. About 20% of patients were lost after consultation; better counseling and follow-up of candidates may be warranted. Expectations and technology limit eligibility for many, especially hyperopes. Low surgery volume may affect training of future refractive surgeons.